(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The mutual fund industry in India is seen to traverse a huge way after its incorporation in the year 1963. It is seen that the industry has experienced significant growth in terms of different parameters such as total houses of fund, total schemes, mobilization of funds, management of assets etc. In face of the crucial role that channels saving of household, a question arises stating whether the mutual industry in India has been successful in attaining the desired goal. The given study is seen to address the said concern. Studies detailed nature states that the industry of mutual fund is seen to record a considerable progress on several fronts which fails to use the potential totally. Based on all parameters, it occurs to deter the economy developed with majority of the economy rising in the world today. Further, the industry is seen to face significant challenges such as ratio of low penetration, absence of product differentiation, poor awareness of investors and lesser ability in communicating customers the desired value, poor interest in retail investors with respect to the industry of mutual funds and emerging the industry nature. On the basis of the analysis, the study further suggests recommendation that would address the given challenges.